Analysis of the Implementation of Article 21 Income Tax Before and After the Application of the Effective Tax Rate under Government Regulation No. 58 of 2023 on Employees’ Taxable Income at CV Lindrif Jaya, Jakarta - Fithrah Kamaliyah; Sri Agustini (Transpublika Publisher, 2026)
This research is motivated by Government Regulation No. 58 of 2023, which introduced the Average Effective Rate (TER) for Article 21 Income Tax withholding effective January 1, 2024. Although the government insists TER is purely administrative, many employees and payroll practitioners view the fluctuating monthly withholdings as a hidden tax increase. This research aims to analyze the impact of calculating Article 21 Income Tax for employees before and after using TER implementation of PP 58/2023 at CV Lindrif Jaya using salary data samples of 5 employees from a total population of 35 employees. The theoretical foundation in this research is tax accounting that focuses on employee income. CV Lindrif Jaya uses income tax calculations based on applicable statutory regulations. The method used is comparative analysis by comparing Article 21 Income Tax calculations based on PP 58 of 2023 with the HPP Law Number 7 of 2021. The findings indicate that implementing the Average Effective Rate does not impose any additional tax burden on employees, despite noticeable fluctuations in monthly withholding amounts over the course of the year. Substantially, the total Article 21 Income Tax payable in one tax year remains the same as under the previous method. This is because a recalculation is performed in the final tax period to ensure that the taxes withheld during the year conform to the actual tax liability based on statutory provisions. Aside from keeping the annual tax burden neutral, TER is also designed to make tax administration easier for employers and withholding agents.